Halogen Scrambling in Pt(II) Substitution Reaction - Sabounchei, S.J. (Asian Journal of Chemistry, 2010)
Addition of NBu4Br to M[PtCI3(PPh3)] in dichloromethane results in a redistribution of halogens and formation of all six isomers of the type M[PtBr3 -xClx(PPh3)], (x = 0,1,2 and 3), which have been identified by 31P-{ 1H} NMR spectroscopy.